Usaha Pemenuhan Kebutuhan dalam Komik Cadavre Exquis Karya PÃ©nÃ©lope Bagieu - , ULFAH IMANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Every living organism will always try to meet all their needs in order to survive. The types of needs found in Cadavre Exquis comic can be classified into two, namely biological needs and psychological needs. Biological needs consist of the need for eating, drinking, and sex. While psychological needs are the needs that are complementary, such as the need for security, the need for love and belonging, the need for self-esteem, and later is the need for self-actualization. Research on the needs was analyzed using the theory of Abraham Maslow's hierarchy of needs. Human beings are intelligent and virtuous, these are what distinguish man from other creatures. However, it does not mean that humans and animals are completely different without any similarity. Humans have instincts, as well as the animals. Instinct is an innate behavior, innate behavior is innate impulse or desire to do something. This impulse directs human behavior to meet their needs levels which will continue to grow with age. On the other hand, motive is obvious actions as the attempt to fulfill needs based on impulse and needs. A variety of motives that underlie all behaviors of the characters in Cadavre Exquis comic have their own purpose as each character has different needs and motivations. Motive can be divided into two, the first is primary motive, namely motive of hunger, thirst, rest, physical contact, and breathing. Next is secondary motive consisting of a motive to have a life partner, social relations, acceptance of others, interpersonal relationships, appreciation, and freedom. A description of the motive was clarified using Martin Handokoâs motivation diagrams theory. While iconicity was used to help analyzing visual and verbal signs in the whole comic.